Navigating Academia During COVID-19 Perspectives and Strategies from BIPOC Women - Njoku, Anuli; Evans, Marian (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This edited volume provides personal narratives of a diverse group of scholars in academia regarding strategies to navigate academia during times of COVID-19 and unrest. Black, Indigenous, and People of Color (BIPOC) women in academia are grappling with emotional tolls and invisible burdens, discrimination, political turmoil, social unrest, and public health crises. Moreover, the rapid pivot response to COVID-19 has exacerbated inequities among BIPOC women in academia. This book explores their stories of ordeal, triumph, loss, and hope. Anuli Njoku is Associate Professor of Public Health in the Department of Public Health at Southern Connecticut State University, USA. Her research and teaching specialties include cultural competency in higher education, health disparities, health promotion and education, health equity, environmental health, rural health, and the scholarship of teaching and learning. Marian Evans is Associate Professor of Public Health in the Department of Public Health, and affiliated faculty in the Department of Women and Gender Studies at Southern Connecticut State University, USA. Her research and teaching specialties include Women's health, environmental health, the scholarship of teaching and learning, and public health practice and management.
Part I Recognizing the Inequities: Amplifying Our Voices -- Self-Identification in Black, Red, Brown, and White: A Clarion Call to Address Medical Racism in Native American Communities -- The Gift of Ontological Inquiry -- Lessons for My Daughters (Taught to Me by bell) -- Celebrating Ramadan During COVID -- Grief and Bereavement During COVID-19: Funeralization and Ritual Losses -- Reimagining Asian Women Scholars in Academic Spaces -- Working Around the Clock in the Time of COVID-19 -- Experiences of a Latina Educator, Mother, and Student During the COVID-19 Pandemic -- Some Time with Writing -- Part II Turning Challenges into Opportunities: Building Resilience -- Grow Through What You Go Through -- Social-Emotional Challenges in K-12 Education During the COVID-19 Pandemic -- Leading in Color in Academia: A Latinx Chair's Experience of Resiliency and Hope -- Navigating Realities While Maintaining Perspective During COVID -- Giving Up Is Never an Option: Personal and Professional Development During COVID-19 -- Redefining Resilience and Hope: La Lucha Continúa! -- Finding My Way Through a Never-Ending Storm: Leading, Mothering, and Coping with Loss -- Part III Identifying Solutions and Best Practices: Strategies for Success -- The Complications of COVID and Conduct -- Teaching the Calculus of Coronavirus-19 -- It's a Win-Win: Faculty-Mentored Research with Students of Color -- ACEing the Black Trauma of the COVID-19 Pandemic -- Coping Resources and Self-care During COVID-19, Police Brutality, and Social Unrest -- Spaces to Heal: Providing the Table and Seats.
Keywords: Career education; Education, Higher; School management and organization; School administration; Sex; Inclusive education; Career Skills; Higher Education; Organization and Leadership; Gender Studies; Inclusive Education